Increasing entertainment among customer in a restaurant through board game design - Ibrahim, Muhammad Azri; Ab Gani, Muhamad Abdul Aziz; Mohd Shuib, Ahmad Sofiyuddin; Mohd Pahme, Nur Faizah; Saidi Othman, Muhammad Fikri (Universiti Teknologi MARA, Perak, 2025)
Extended waiting times for food in restaurants often contribute to customer dissatisfaction, primarily due to feelings of boredom and a lack of engaging stimulus. This study explores an innovative approach to enhancing the dining experience by integrating board games as a form of interactive entertainment during waiting periods. The primary objectives are to identify types of board games that are suitable for restaurant settings and to determine the key elements that make these games effective as interactive tools within a dining context. Employing a mixed-methods research design, this study combines quantitative data collected through customer surveys with qualitative insights gathered from semi- structured interviews involving restaurant patrons and the restaurant owner. The findings reveal that the presence of board games significantly reduces customer perceived waiting time, fosters social interaction, and enhances the overall dining environment. Customers reported feeling more relaxed, engaged, and satisfied with their dining experience when given the opportunity to play games while waiting. From the restaurant’s perspective, this strategy functions as an indirect method of “buying time,” allowing food to be prepared at its usual pace without compromising service quality. Moreover, the implementation of board games appears to encourage longer stays and repeat visits, contributing positively to the restaurant’s business value. Overall, this study concludes that the integration of board games offers a cost-effective and impactful solution for improving customer satisfaction, enriching the social environment, and redefining waiting time as a meaningful and enjoyable part of the dining experience.